Peningkatan Prestasi Kerja Karyawan Sektor Perbankan Melalui Motivasi Kerja - Kasnaeny K (LP2M IBK Nitro, 2018)
This study aims to determine the types of motivation can boost the performance of employees in the banking sector in the city of Makassar ( Studies in Bank BNI and Bank BRI ) , so that the manager can find a good strategy for motivating employees , in order to excel in competition. Research conducted by distributing questionnaires to employees of BNI and Bank BRI Makassar. The research sample of 30 people , comprising 15 employees of the bank BNI and 15 of BRI. The analytical method used to determine the types of motivation that can improve the performance of banking sector employees , namely by using quantative descriptive analysis method by grouping the results of questionnaire answers and then calculate the frequency of each answer. The analysis showed that the most dominant motivation to encourage employee performance is the motive need for affiliation